Mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenic and preparation method thereof
By adopting a mechanical stacked structure of gallium antimonide and indium gallium arsenic in thermal photovoltaic cells, the problems of current limitation and low reliability of traditional stacked batteries are solved, and more efficient photoelectric conversion and longer service life are achieved.
Patent Information
- Application Number
- CN202411903480.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-08
AI Technical Summary
The current output of traditional stacked thermal photovoltaic cells is limited by the minimum output current, and damage to a certain junction zone may cause the entire battery to fail, reducing the reliability and service life of the system.
The mechanical stacked thermal photovoltaic cell structure based on gallium antimonide and indium gallium arsenic is adopted. The two batteries are connected through mechanical stacking, and the transmission layer of the indium gallium arsenic cell is plated on the back of the gallium antimonide battery to achieve electrical isolation and close contact, and support separate lead output.
Overcome the current limit and reliability problems of traditional stacked batteries, improve spectral utilization efficiency and photoelectric conversion performance, and enhance the stability and service life of the battery system.
Smart Images

Figure CN119789541A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a thermophotovoltaic cell and a preparation method thereof, and in particular to a mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide and a preparation method thereof. Background Art
[0002] Indium gallium arsenide (InGaAs) and gallium antimonide (GaSb) cells are core devices in the field of infrared photoelectric conversion, and their performance has a decisive influence on the spectral utilization efficiency and photoelectric conversion effect. Patent CN103474501A discloses a selective emitter gallium antimonide infrared cell and its preparation method. The gallium antimonide material has a bandgap width of 0.72 electron volts (eV). The gallium antimonide cell prepared by the zinc diffusion method can effectively absorb light waves with a wavelength within 1750 nanometers, but cannot utilize the spectrum with a wavelength exceeding 1750 nanometers. Patent CN116454146A discloses a self-focusing long-wave mismatched InGaAs cell and its preparation method. By epitaxially growing lattice-mismatched indium gallium arsenide materials on an indium phosphide (InP) substrate, an indium gallium arsenide cell with a bandgap width range of 0.5-0.7 electron volts can be prepared. The wavelength of the light wave absorbed can reach up to 2500 nanometers, thus covering a wider spectral range.
[0003] In order to further improve the spectral utilization efficiency and photoelectric performance, existing technologies have attempted to combine multiple cells in a stacked or multi-junction form. For example, patent CN112736200A connects two different cells in series through a stacked structure; patent CN108735848 proposes an AlGaAs multi-junction stacked cell. In addition, the document "Thermophotovoltaicefficiency of 40%" (LaPotin et al., Nature, 604, 287–291, 2022) also mentions InGaAs double-junction cells. However, although these multi-junction and stacked cell designs have improved the spectral utilization efficiency to a certain extent, due to the limitations of the series mode, their output current is limited to the minimum current, and damage to any junction area may cause the entire battery to fail, reducing the reliability and service life of the system. In addition, in the application scenario of thermophotovoltaic energy storage output, the spectral absorption characteristics of a certain junction area do not match due to changes in the radiator temperature, which further exacerbates the problem of the output current being limited by the minimum current and reduces the overall efficiency and stability of the battery. Summary of the invention
[0004] Purpose of the invention: In view of the above problems, the present invention proposes a mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide and a preparation method thereof, which solves the problem that the current output of traditional laminated cells is limited by the minimum output current and the overall failure caused by damage to a certain junction area.
[0005] Technical solution: The technical solution adopted by the present invention is a mechanically stacked thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide, which comprises a gallium antimonide cell and an indium gallium arsenide cell mechanically stacked and connected from top to bottom; the two cells are electrically isolated, and the two cells are respectively provided with positive and negative electrodes and are led out separately;
[0006] The gallium antimonide cell comprises a gallium antimonide substrate, an emitter is arranged inside the gallium antimonide substrate near the upper surface, and the upper and lower surfaces of the gallium antimonide substrate have embedded positive and negative electrodes, and the positions of the positive electrode and the negative electrode are aligned one by one; a silicon nitride antireflection layer is deposited on the upper and lower surfaces of the gallium antimonide substrate respectively, and a silicon nitride transmission layer is also arranged under the silicon nitride antireflection layer on the back of the gallium antimonide substrate;
[0007] The InGaAs cell comprises an InP substrate, on the upper surface of which a series of buffer layers, transition layers and functional layers are sequentially grown, wherein the functional layer is an InGaAs epitaxial layer, on the upper surface of which a tungsten-doped InOx transparent conductive layer is provided as a positive electrode, and on the back of the InP substrate a negative electrode is provided.
[0008] The back silicon nitride transmission layer of the gallium antimonide cell and the tungsten-doped indium oxide transparent conductive layer of the indium gallium arsenide cell are fixedly connected by thermal curing glue at the edges.
[0009] The thickness of the tungsten-doped indium oxide transparent conductive layer is 380-420 nm, and the doping mass percentage of the tungsten-doped indium oxide is 4.0%-5.0% tungsten oxide WO 3 The optical transmittance of the tungsten-doped indium oxide film of the tungsten-doped indium oxide transparent conductive layer in the wavelength range of 1750nm to 2500nm exceeds 75%.
[0010] The thickness of the silicon nitride anti-reflection layer is 180-200 nm; the thickness of the silicon nitride transmission layer is 280-320 nm.
[0011] Double-sided photolithography and precise etching processes are used to etch out the gate line positions of the positive and negative electrodes of the gallium antimonide battery, and the gate lines of the positive and negative electrodes are aligned one by one in the vertical direction to avoid the electrodes blocking photons and improve the overall photoelectric conversion efficiency.
[0012] The front of the GaSb cell is deposited with a tin / platinum / silver composite electrode, and the back of the GaSb cell is deposited with a titanium / platinum / silver composite electrode; the negative electrode of the InGaAs cell uses a gold / nickel / gold composite electrode.
[0013] The present invention proposes a method for preparing a mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide, comprising: preparing a gallium antimonide cell; preparing an indium gallium arsenide cell; and realizing a mechanical laminated structure;
[0014] The preparation of the gallium antimonide battery comprises the following steps:
[0015] (1) Cleaning tellurium doping concentration is 1~3×10 17 cm -3 , crystal orientation is <100> N-type GaSb wafers and remove surface oxides;
[0016] (2) forming a P-type emitter on the front and back sides of the GaSb wafer by diffusion, and removing the P-type layer on the back side by using a tartaric acid-based etching solution;
[0017] (3) using a magnetron sputtering method to deposit a silicon nitride antireflection layer on the upper and lower surfaces of the gallium antimonide wafer after preparing the emitter, respectively, to obtain a coated gallium antimonide wafer;
[0018] (4) using double-sided photolithography and precision etching processes to etch the opening positions of the positive and negative electrodes on the front and back sides of the coated GaSb wafer; the depth of the back opening reaches 2.5±0.3 μm in the GaSb wafer; the precision of the precision etching is ±0.1 μm;
[0019] (5) using electron beam evaporation technology to evaporate positive and negative electrodes on the front and back sides of the photolithographic GaSb wafer;
[0020] (6) further depositing a silicon nitride transmission layer on the back side of the gallium antimonide wafer after the electrode is prepared;
[0021] The preparation of the indium gallium arsenide battery comprises the following steps:
[0022] (1) The sulfur concentration of cleaning is 3 to 4×10 18 cm -3 After removing the surface oxide, the InPAs buffer layer and the multi-layer transition layer are grown in sequence by chemical vapor deposition.
[0023] (2) Growth of In on the transition layer 0.68 Ga 0.32 As cell PN junction, and grow InPAs window layer and heavily doped InGaAs layer as functional layer;
[0024] (3) depositing a tungsten-doped indium oxide transparent conductive layer on the surface of the functional layer by direct current magnetron sputtering;
[0025] (4) evaporating a negative electrode on the back of the indium phosphide substrate;
[0026] The realization of the mechanical stacked structure comprises the following steps:
[0027] (1) Perform ultrasonic cleaning on GaSb batteries and InGaAs batteries to remove residual particles on the surface;
[0028] (2) applying a thermal curing adhesive to the edge of the anti-reflection layer on the back of the GaSb cell, aligning and fixing the transparent conductive layer of the InGaAs cell with the anti-reflection layer;
[0029] (3) After applying pressure using a special fixture, cure at 100 to 120°C for 20 to 30 minutes.
[0030] The method also includes (4) after the stacking is completed, the positive and negative electrodes of the GaSb battery and the InGaAs battery are separately led out by wire welding.
[0031] Double-sided photolithography and precision etching processes are used to etch the opening positions of the positive and negative electrodes on the front and back of the coated GaSb wafer, including: uniformly coating the upper and lower surfaces of the coated GaSb wafer with photoresist, and using double-sided alignment exposure and development technology to align the positive and negative electrodes on the upper and lower surfaces; reducing the shielding of the electrodes from light. The silicon nitride layer in the exposed area is etched using hydrofluoric acid and ammonium fluoride solution, and the etching rate is controlled to be as low as about 0.38 microns per minute to ensure that the electrode opening position is clear. After the first etching is completed, photoresist is coated on the front surface again, and the back substrate layer is etched twice using a tartaric acid-based etching solution to accurately form the back electrode area to ensure the structural integrity and functionality of the electrode.
[0032] The preparation step (1) of the indium gallium arsenide battery comprises: using a sulfur-containing concentration of 3 to 4×10 18 cm -3 , <100> The crystal N-type indium phosphide (InP) was used as the substrate material, and was successively placed in acetone, isopropanol, and alcohol for cleaning, and then the oxide on the surface of the wafer was removed with dilute hydrochloric acid. After cleaning in deionized water, it was blown dry with nitrogen and finally thermally baked. A layer of InPAs buffer layer was grown on the InP substrate by chemical vapor deposition, and then 6 layers of InPxAs1-x transition layers were grown on the upper surface of the InPAs buffer layer, and the arsenic content gradually increased from 0.05±0.01 to 0.3±0.01.
[0033] Beneficial effects: Compared with the prior art, the present invention has the following advantages: (1) A mechanical laminated thermophotovoltaic cell structure is designed, in which two cells are electrically isolated and stacked up and down. This structure supports separate lead output, which not only overcomes the current limitation of the traditional series design, but also avoids the absorption characteristic mismatch problem caused by the temperature change of the radiator, ensuring the stability and reliability of the device under complex temperature conditions. Through this innovative structural design, the performance and service life of the photoelectric conversion device can be further improved, and the damage resistance of the system can be significantly improved. Stacking gallium antimonide cells and indium gallium arsenide cells in a laminated structure can achieve efficient division of labor and utilization of the spectrum under the same radiation conditions. Gallium antimonide cells mainly absorb high-energy short-wave photons, while low-energy long-wave photons can pass through the gallium antimonide cells and be absorbed and converted by the indium gallium arsenide cells on the lower layer. (2) By coating a layer of indium gallium arsenide cell antireflection layer on the back of the gallium antimonide cell, close contact between the two cells is achieved, while the transmittance and absorption efficiency of photons are improved. InGaAs cells use a tungsten-doped indium oxide transparent conductive layer as the positive electrode, combined with an anti-reflection layer on the back of GaSb, to avoid the formation of an air layer during the stacking process, effectively reducing photon loss and improving stacking efficiency. (3) The present invention also proposes a new preparation method for this mechanical laminated thermophotovoltaic cell structure. By using double-sided photolithography and selective evaporation processes at the positive and negative electrodes of the GaSb cell, and embedding the grid lines on the back of the cell into the cell through etching technology, the current collection path is optimized and the carrier collection efficiency is improved. In summary, the present invention improves the spectral utilization efficiency and photoelectric conversion performance, enhances the reliability of the battery system, and realizes efficient absorption and conversion of wide-band photons. The present invention overcomes the shortcomings of traditional laminated or multi-junction cells in current limitation, light loss and reliability, and provides an efficient, reliable and easy-to-manufacture laminated photovoltaic solution, which is suitable for infrared spectrum power generation and thermophotoelectric isotope power supply, heat pipe stack power supply and other high-efficiency thermophotovoltaic application scenarios. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the structure of the mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide according to the present invention;
[0035] Figure 2 It is a structural diagram of gallium antimonide and indium gallium arsenide batteries in the present invention;
[0036] Figure 3 This is a schematic diagram of the preparation process of the gallium antimonide battery described in the present invention;
[0037] Figure 4 The graph is an external quantum efficiency graph of gallium antimonide and indium gallium arsenide cells prepared in the present invention, wherein curve a is an external quantum efficiency curve of the gallium antimonide cell, and curve b is an external quantum efficiency curve of the indium gallium arsenide cell;
[0038] Figure 5is a spectral transmittance graph of the present invention, wherein curve c is a spectral transmittance curve of a gallium antimonide cell, and curve d is a transmittance curve of a transparent conductive layer in an indium gallium arsenide cell;
[0039] Figure 6 This is a diagram of the external quantum efficiency of the mechanical laminated thermophotovoltaic cell in Example 1 of the present invention;
[0040] Figure 7 is a component diagram of a mechanical laminated thermophotovoltaic cell of comparative experiment 1 of the present invention;
[0041] Figure 8 is a component diagram of a mechanical laminated thermophotovoltaic cell of comparative experiment 2 of the present invention;
[0042] Fig. 9 This is a component diagram of a mechanical laminated thermophotovoltaic cell in Comparative Example 1 of the present invention;
[0043] Fig.10 This is a component diagram of the mechanical laminated thermophotovoltaic cell in Comparative Example 2 of the present invention.
[0044] Explanation of the figure numbers: 1: radiator; 2: gallium antimonide substrate; 3: emitter; 4: silicon nitride antireflection layer; 5: negative electrode; 6: positive electrode; 7: silicon nitride transmission layer; 8: indium phosphide substrate; 9: functional layer; 10: tungsten-doped indium oxide transparent conductive layer; 11: negative electrode; S1: gallium antimonide cell; S2: indium gallium arsenic cell. DETAILED DESCRIPTION
[0045] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0046] Example 1
[0047] The mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide described in the present invention comprises a gallium antimonide cell and an indium gallium arsenide cell. Figure 1 The schematic diagram of the structure of the mechanical laminated thermophotovoltaic cell of the present invention is given. The radiator 1 provides the radiation spectrum and effectively transmits it to the surface of the InGaAs cell S2 through the GaSb cell S1. The two cells are electrically isolated and stacked up and down, and the positive and negative electrodes are led out separately. Figure 2As shown, the upper surface of the gallium antimonide substrate 2 of the gallium antimonide cell S1 is provided with an emitter 3, and the gallium antimonide cell S1 has an embedded positive and negative electrode structure, the positive electrode 6 and the negative electrode 5 are respectively etched out of precise positions by a double-sided photolithography process, and a 190nm thick silicon nitride anti-reflection layer 4 is deposited on the upper and lower surfaces respectively, and a 300nm thick silicon nitride transmission layer 7 is further plated on the back; the indium gallium arsenide cell S2 sequentially grows a series of buffer layers, transition layers and functional layers 9 on the upper surface of the indium phosphide substrate 8, and finally deposits a tungsten-doped indium oxide transparent conductive layer 10 on the surface of the indium gallium arsenide epitaxial layer as a positive electrode, with a thickness of 400nm, and a gold / nickel / gold composite electrode is used as a negative electrode 11 on the back; the two cells are connected by mechanical stacking, and the back transmission layer of the gallium antimonide cell S1 and the transparent conductive layer of the indium gallium arsenic cell S2 are precisely aligned and fixed by thermal curing glue.
[0048] The electrodes and gate lines on the front and back sides are highly aligned to ensure that photons are not blocked by the electrodes when passing through the GaSb cell and can pass smoothly to the InGaAs cell, thereby achieving efficient absorption and conversion of long-wave photons.
[0049] A transmission layer of InGaAs cell is evaporated on the back of GaSb cell, which not only improves the close contact and photon transmittance of the two cells during the stacking process, but also uses the transmission layer as an insulating layer to ensure electrical isolation between the two cells, thereby supporting independent lead output design.
[0050] The present invention introduces a tungsten-doped indium oxide transparent conductive layer as the positive electrode in the indium gallium arsenide battery. The transparent conductive layer has a transmittance of more than 75% in the visible and near-infrared bands, which can maximize the utilization efficiency of long-wave photons, and has a resistivity as low as 1.8×10 -4 Ω·cm, which can efficiently transmit current. At the same time, it is closely combined with the transmission layer on the back of the GaSb cell to avoid the formation of air interlayers during the stacking process, thereby further improving the transmittance of photons and stacking efficiency. The use of tungsten-doped indium oxide transparent conductive layer overcomes the shielding of light by traditional metal electrodes.
[0051] Example 2
[0052] The method for preparing the mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide of the present invention comprises the following steps:
[0053] (1) Preparation of GaSb batteries;
[0054] (2) Preparation of InGaAs batteries;
[0055] (3) Mechanical stacking and leads.
[0056] The preparation process of GaSb battery is as follows Figure 3 As shown, the preparation steps specifically include the following:
[0057] The first step is to select the tellurium Te doping concentration between 1-3×10 17 cm -3 , the crystal direction is <100> The N-type gallium antimonide wafer is used as the substrate. First, the wafer is placed in acetone and isopropanol for ultrasonic cleaning in turn to remove organic pollutants on the surface. Subsequently, the wafer is immersed in 15% dilute hydrochloric acid to remove the oxide layer on the surface of the substrate; after the cleaning is completed, it is rinsed with deionized water, blown dry with nitrogen, and then baked in a clean environment to remove residual moisture on the surface, thereby obtaining a clean gallium antimonide substrate 2.
[0058] In the second step, the GaSb substrate 2 processed in the first step is placed in the quartz diffusion tube of the tubular diffusion furnace, and 7.5 grams of zinc-gallium alloy containing 5% zinc concentration is added as a diffusion source. The diffusion tube is evacuated, and high-purity argon is slowly filled in after the vacuum degree is lower than 5Pa until the pressure inside and outside the tube is balanced, and the argon flow rate is adjusted to 1.5L / min. The temperature of the diffusion tube is raised to 550℃ at a heating rate of 10℃ / min, and the constant temperature is maintained for 1.5 hours to achieve the diffusion of zinc atoms to the surface of the substrate and form a uniform P-type layer. After the diffusion is completed, the insulation layer of the diffusion furnace is quickly removed, the diffusion tube is cooled to room temperature, and the diffused GaSb wafer is taken out, and a P-type diffusion layer has been formed on its surface; a layer of photoresist is coated on the front of the diffused GaSb wafer to protect the P-type layer formed on the front. Subsequently, the wafer is immersed in a specific ratio of etching solution to remove the excess P-type diffusion layer on the back and periphery of the wafer. The etching solution formula is 3.5g tartaric acid, 4mL hydrogen peroxide, 1mL hydrofluoric acid, and 400mL deionized water. The etching time is controlled at 1-3 minutes, and the progress is monitored in real time to ensure that the etching is uniform and does not damage the front P-type layer. After the etching is completed, the wafer is immersed in an acetone solution to remove the photoresist, and finally rinsed with deionized water and dried with nitrogen to obtain a gallium antimonide wafer with no excess P-type layer on the back and a P-type emitter region 3 on the front.
[0059] The third step is to place the GaSb wafer diffused in the second step into the magnetron sputtering chamber and use high-purity silicon target material to perform silicon nitride (Si nitride) on both sides of the wafer. 3 N 4 ) layer. First, the chamber is evacuated to 1×10 -5 Pa, to ensure the purity of the deposition environment, and then heat the chamber to 150 ° C to reduce the internal stress of the film and improve the quality of the film. 95 sccm of argon and 6 sccm of nitrogen were introduced, and the total pressure in the chamber was adjusted to 1.3 Pa to provide a stable working atmosphere. Magnetron sputtering was carried out under the condition of 150W RF power supply, and the deposition rate was controlled to 2nm / min. By accurately adjusting the time, a 190nm thick silicon nitride layer 4 was deposited on both sides of the wafer.
[0060] The fourth step is to coat the upper and lower surfaces of the gallium antimonide wafer on which silicon nitride was deposited in the third step with photoresist, and accurately align and match the photolithography mask patterns on the upper and lower surfaces through double-sided exposure technology to ensure that the photolithography patterns are highly aligned at the positive and negative electrodes and the gate line openings. Subsequently, exposure and development treatments are performed to remove the photoresist at the reserved gate line and electrode positions to reveal the silicon nitride area that needs to be etched. The treated wafer is immersed in an etching solution with a ratio of 30g ammonium fluoride: 5mL hydrofluoric acid: 50mL deionized water, and the silicon nitride layer at the gate line and electrode positions is removed by wet etching to ensure that a clear opening area is exposed. The hydrofluoric acid and ammonium fluoride solution etches the silicon nitride layer in the exposed area at a corrosion rate of 0.66 microns per minute. After etching is completed, the front surface is coated with photoresist again for protection, and then the back of the wafer is immersed in a tartaric acid-based etching solution (the etching solution formula is 3.5g tartaric acid, 4mL hydrogen peroxide, 1mL hydrofluoric acid, and 400mL deionized water) to achieve deep etching of the back of the wafer. The precise etching rate of the tartaric acid-based etching solution is 0.38μm / min, and the etching depth reaches 2.5μm. After etching is completed, the wafer is cleaned and dried, and clear and precise gate lines and electrode openings are formed on both sides of the wafer.
[0061] Step 5: Electron beam evaporation is used to deposit metal electrodes on both the front and back sides of the wafer in step 4. First, 50nm of titanium (Ti), 50nm of platinum (Pt), and 2.5μm of silver (Ag) are sequentially deposited on the back side of the wafer as the negative electrode 5 of the gallium antimonide battery, and then 50nm of tin (Sn), 50nm of platinum (Pt), and 3μm of silver (Ag) are sequentially deposited on the front side as the positive electrode 6 of the battery.
[0062] Step 6: Place the back of the battery prepared in step 5 into a magnetron sputtering chamber to coat 300nm of silicon nitride 7. After deposition, take the wafer out of the chamber and clean the back with deionized water and anhydrous ethanol in a clean environment to remove any remaining particles and micro-pollutants from the deposition process, and finally blow dry with nitrogen to ensure that the back is clean and free of any contamination, ready for the next stacking process.
[0063] The preparation process of InGaAs battery specifically includes the following preparation steps:
[0064] The first step is to select sulfur (S) doping concentration of 4×10 18 cm -3, the crystal direction is <100> The N-type indium phosphide (InP) wafer 8 is used as the substrate. First, the wafer is placed in isopropanol, acetone and alcohol for ultrasonic cleaning in turn, and each solution is cleaned for 5 minutes to remove surface organic matter and impurities. Subsequently, the cleaned wafer is placed in a 5% dilute hydrochloric acid solution for treatment to remove the natural oxide layer on the surface. After cleaning, the wafer is thoroughly cleaned with deionized water and then blown dry with nitrogen to ensure that there is no residual moisture on the surface. Finally, the wafer is placed on a hot plate and baked at 180°C for 10 minutes; then, the cleaned and dried indium phosphide substrate is placed in the reaction chamber of the chemical vapor deposition equipment and fixed on the substrate table. By precisely controlling the vapor deposition parameters, a series of buffer layers, transition layers and functional layers are grown in sequence. First, an N-type InP buffer layer with a thickness of 400nm is grown on the substrate, containing a silicon (Si) carrier concentration of 5×10 -17 cm -3 ; Then grow five transition layers, including 400nm thick N-type InP 0.95 As 0.05 、InP 0.9 As 0.1 、InP 0.85 As 0.15 、InP 0.8 As 0.2 and InP 0.75 As 0.25 , each layer contains silicon (Si) carrier concentration of 5×10 -17 cm-3, by gradually adjusting the As content to achieve lattice buffer from InP to InGaAs; then grow 1000nm thick N-type InP 0.7 As 0.3 The sixth transition layer contains tellurium (Te) with a carrier concentration of 1×10 -19 cm -3 The construction of the functional layer includes growing a 300nm thick N-type In 0.68 Ga 0.32 As base layer, containing tellurium (Te) carrier concentration of 3×10 - 18 cm -3 ; Then grow 3000nm thick P-type In 0.68 Ga 0.32 As emitter layer, containing zinc (Zn) carrier concentration of 2×10 -17 cm -3 ; Then grow 500nm thick P-type InP 0.7 As 0.3 The window layer contains zinc (Zn) with a carrier concentration of 2×10 -18 cm -3 ; Finally, grow a 50nm thick P-type In layer on the surface0.68 Ga 0.32 As front contact layer, containing zinc (Zn) carrier concentration of 3×10 -19 cm -3 .
[0065] In the second step, a tungsten-doped indium oxide transparent conductive layer is deposited on the surface of the epitaxially grown InGaAs epitaxial layer 9 by using magnetron sputtering technology, using a ceramic target (made of indium oxide In 2 O 3 Tungsten oxide WO doped with 5.0% by mass 3 First, the chamber was evacuated to 2×10 -4 Pa, and pre-sputter the target for 20 minutes to clean the target surface and stabilize the deposition conditions. The temperature in the chamber was controlled at 300 ° C, and a mixed gas of 95 sccm argon and 6 sccm oxygen was introduced at the same time. The total gas pressure was adjusted to 0.6 Pa, and the DC power density was set to 1.65 W / cm 2 The deposition rate was 2 nm / min and the deposition time was precisely controlled to form a 400 nm thick tungsten-doped indium oxide film 10 on the substrate surface.
[0066] In the third step, the back of the substrate of the InGaAs battery in the second step is deposited with 10nm thick gold (Au), 10nm thick nickel (Ni) and 3μm thick gold (Au) in sequence by electron beam evaporation, as the negative electrode 11 of the InGaAs battery. After the evaporation is completed, the battery is moved to a clean environment, and the back is cleaned with deionized water and anhydrous ethanol to remove the microparticles or contaminants that may remain during the evaporation process, and then blown dry with nitrogen to ensure that the back surface is clean and free of pollution.
[0067] The specific process of mechanical stacking and lead-in is:
[0068] First, the surface of the GaSb cell and InGaAs cell was cleaned separately, and ultrasonic cleaning with deionized water and anhydrous ethanol was used to remove residual particles and organic matter, ensure surface cleanliness and enhance interface adhesion. A circle of thermal curing glue was applied to the edge of the anti-reflection layer on the back of the GaSb cell, and then the transparent conductive layer of the InGaAs cell was precisely aligned with the anti-reflection layer on the back of the GaSb cell, and pressure was gradually applied in a special pressure fixture to ensure close contact between the two cells. After stacking, they were cured in an environment of 120°C for 30 minutes. After stacking, the positive and negative electrodes of the GaSb cell and InGaAs cell were respectively wire-welded using a gold wire welding machine.
[0069] Figure 4In the figure, curves a and b are the external quantum efficiency curves of GaSb and InGaAs cells, respectively. It can be found that the GaSb cell prepared by the present invention has a high absorption efficiency for short-wave high-energy photons, mainly absorbing the spectrum with a wavelength of 400nm to 1750nm; while the InGaAs cell has a high utilization rate for long-wave low-energy photons, mainly absorbing the spectrum from 1750nm to 2400nm. Figure 5 In the figure, curve c is the transmittance of the GaSb cell, and the transmittance of the GaSb cell for the spectrum in the wavelength range of 1750nm to 2400nm is above 95%, and curve d is the transmittance of the IWO conductive layer on the front surface of the InGaAs cell, and its transmittance in the main absorption band of the InGaAs cell (1750nm to 2400nm) is about 75%. Therefore, in the wide-band high-efficiency mechanical laminated thermophotovoltaic cell based on GaSb and InGaAs of the present invention, the GaSb cell mainly absorbs short-wave high-energy photons, and allows long-wave low-energy photons to pass through and be transmitted to the InGaAs cell, realizing the division of labor absorption and high-efficiency conversion of wide-band photons. Figure 6 In the figure, curve e is the quantum efficiency curve of a wide-spectrum high-efficiency mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide according to the present invention.
[0070] Comparative experiment 1:
[0071] In this comparative experiment, Figure 7 As shown, the preparation steps of the InGaAs battery are basically the same as those in Example 1, but the negative electrode of the GaSb battery in the sample is not evaporated into the interior of the substrate during the preparation process, but the negative electrode is directly exposed to the outside, and a 300nm silicon nitride layer is not plated on the back as a transmission and protective layer. Fig. 9 In the figure, curve f is the quantum efficiency curve of the laminated thermophotovoltaic cell in comparative example 1 of the present invention. It can be seen from the figure that there is no silicon nitride transmission layer to isolate the GaSb and InGaAs cells, the positive and negative electrodes of the two cells are connected to form a series circuit, and there is an air layer in the connecting part of the electrodes, so that the quantum efficiency in this comparative experiment 1 is less than 70% in the useful band of 1000-2000nm.
[0072] Comparative experiment 2:
[0073] In this comparative experiment, Figure 8 As shown, the preparation steps of the gallium antimonide battery are basically the same as those in Example 1, but during the preparation process of the indium gallium arsenide battery in the sample, the positive electrode does not use a tungsten-doped indium oxide transparent conductive layer, but uses a traditional metal electrode (20nm titanium Ti, 40nm platinum Pt, 4μm gold Au). Fig.10In the figure, curve g is the quantum efficiency curve of the laminated thermophotovoltaic cell in comparative example 2 of the present invention. As can be seen from the figure, in comparative experiment 2, the GaSb and InGaAs cells are separated by a silicon nitride transmission layer, and the two cells can output electrical energy separately, but no transparent conductive layer is used, but a traditional metal electrode is used, resulting in an air layer in the part where the electrodes are connected, and most of the light waves projected from the GaSb cell are reflected by the metal electrode, resulting in a lot of energy loss, so that the quantum efficiency in this comparative experiment 2 is only 30% in the 1700-2200nm band.
Claims
1. A mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide, characterized in that: The battery comprises a gallium antimonide battery (S1) and an indium gallium arsenide battery (S2) which are mechanically stacked and connected from top to bottom; the two batteries are electrically isolated, and the two batteries are respectively provided with positive and negative electrodes and are each led out separately; The gallium antimonide cell (S1) comprises a gallium antimonide substrate (2), an emitter (3) is provided inside the gallium antimonide substrate (2) near the upper surface, and the upper and lower surfaces of the gallium antimonide substrate (2) have embedded positive and negative electrodes (5), and the positions of the positive electrode (6) and the negative electrode (5) are aligned one by one; a silicon nitride antireflection layer (4) is deposited on the upper and lower surfaces of the gallium antimonide substrate (2), respectively, and a silicon nitride transmission layer (7) is provided below the silicon nitride antireflection layer on the back of the gallium antimonide substrate; The indium gallium arsenide battery (S2) comprises an indium phosphide substrate (8), a series of buffer layers, transition layers and functional layers (9) are sequentially grown on the upper surface of the indium phosphide substrate (8), the functional layer (9) being an indium gallium arsenide epitaxial layer, a tungsten-doped indium oxide transparent conductive layer (10) being provided on the upper surface of the indium gallium arsenide epitaxial layer as a positive electrode, and a negative electrode (11) being provided on the back side of the indium phosphide substrate (8).
2. The mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide according to claim 1, characterized in that: The back silicon nitride transmission layer (7) of the gallium antimonide cell and the tungsten-doped indium oxide transparent conductive layer (10) of the indium gallium arsenide cell are fixedly connected via thermal curing glue at the edges.
3. The mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide according to claim 1, characterized in that: The thickness of the tungsten-doped indium oxide transparent conductive layer (10) is 380-420 nm, the doping mass percentage of the tungsten-doped indium oxide is 4.0%-5.0% of tungsten oxide WO3, and the optical transmittance of the tungsten-doped indium oxide film of the tungsten-doped indium oxide transparent conductive layer (10) in the wavelength band of 1750 nm to 2500 nm exceeds 75%.
4. The mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide according to claim 1, characterized in that: The thickness of the silicon nitride anti-reflection layer is 180-200 nm; the thickness of the silicon nitride transmission layer is 280-320 nm.
5. The mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide according to claim 1, characterized in that: Double-sided photolithography and precise etching processes are used to etch out the grid lines of the positive and negative electrodes of the GaSb battery, and align the grid lines of the positive and negative electrodes one by one in the vertical direction.
6. The mechanically laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide according to claim 1, characterized in that: The front of the gallium antimonide battery (S1) is vapor-deposited with a tin / platinum / silver composite electrode, and the back of the gallium antimonide battery (S1) is vapor-deposited with a titanium / platinum / silver composite electrode; the negative electrode (11) of the indium gallium arsenide battery (S2) uses a gold / nickel / gold composite electrode.
7. A method for preparing a mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide, characterized in that: include: Preparation of GaSb batteries; Preparation of InGaAs batteries; and the realization of mechanical laminated structures; The preparation of the gallium antimonide battery comprises the following steps: (1) Cleaning tellurium doping concentration is 1~3×10 17 cm -3 , crystal orientation is <100> N-type GaSb wafers and remove surface oxides; (2) forming a P-type emitter on the front and back sides of the GaSb wafer by diffusion, and removing the P-type layer on the back side by using a tartaric acid-based etching solution; (3) using a magnetron sputtering method to deposit silicon nitride antireflection layers on the upper and lower surfaces of the gallium antimonide wafer after the emitter is prepared, respectively, to obtain a coated gallium antimonide wafer; (4) using double-sided photolithography and precision etching processes to etch the opening positions of the positive and negative electrodes on the front and back sides of the coated GaSb wafer; wherein the depth of the back opening reaches 2.5 μm ± 0.3 μm in the GaSb wafer; and the precision of the precision etching is ± 0.1 μm; (5) using electron beam evaporation technology to evaporate positive and negative electrodes on the front and back sides of the photolithographic GaSb wafer; (6) further depositing a silicon nitride transmission layer on the back side of the gallium antimonide wafer after the electrode is prepared; The preparation of the indium gallium arsenide battery comprises the following steps: (1) The sulfur concentration of cleaning is 3 to 4×10 18 cm -3 After removing the surface oxide, the InPAs buffer layer and the multi-layer transition layer are grown in sequence by chemical vapor deposition. (2) Growth of In on the transition layer 0.68 Ga 0.32 As cell PN junction, and grow InPAs window layer and heavily doped InGaAs layer as functional layer; (3) depositing a tungsten-doped indium oxide transparent conductive layer on the functional surface by direct current magnetron sputtering; (4) evaporating a negative electrode on the back of the indium phosphide substrate; The realization of the mechanical stacked structure comprises the following steps: (1) Perform ultrasonic cleaning on GaSb batteries and InGaAs batteries to remove residual particles on the surface; (2) applying a thermal curing adhesive to the edge of the anti-reflection layer on the back of the GaSb cell, aligning and fixing the transparent conductive layer of the InGaAs cell with the anti-reflection layer; (3) After applying pressure using a special fixture, cure at 100 to 120°C for 20 to 30 minutes.
8. The method for preparing a mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide according to claim 7, characterized in that: The method also includes (4) after the stacking is completed, the positive and negative electrodes of the GaSb battery and the InGaAs battery are separately led out by wire welding.
9. The method for preparing a mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide according to claim 7, characterized in that: Double-sided photolithography and precision etching processes are used to etch the opening positions of the positive and negative electrodes on the front and back sides of the coated gallium antimonide wafer, including: evenly coating the upper and lower surfaces of the coated gallium antimonide wafer with photoresist, aligning the positions of the positive and negative electrodes on the upper and lower surfaces using double-sided alignment exposure and development technology; etching the silicon nitride layer in the exposed area once using hydrofluoric acid and ammonium fluoride solution, then coating the front surface with photoresist, and using tartaric acid-based etching solution to perform a second etching on the back substrate layer.
10. The method for preparing a mechanical laminated thermophotovoltaic cell based on gallium antimonide and indium gallium arsenide according to claim 7, characterized in that: The preparation step (1) of the indium gallium arsenide battery comprises: using a sulfur-containing concentration of 3 to 4×10 18 cm -3 , <100> The crystal N-type indium phosphide (InP) was used as the substrate material, and was successively placed in acetone, isopropanol, and alcohol for cleaning, and then the oxide on the surface of the wafer was removed with dilute hydrochloric acid. After cleaning in deionized water, it was blown dry with nitrogen and finally thermally baked. A layer of InPAs buffer layer was grown on the InP substrate by chemical vapor deposition, and then 6 layers of InPxAs1-x transition layers were grown on the upper surface of the InPAs buffer layer, and the arsenic content gradually increased from 0.05±0.01 to 0.3±0.01.
Citation Information
Patent Citations
Selective emitter gallium antimonide infrared battery and manufacturing method thereof
CN103474501A
Laminated cell and preparation method and application thereof
CN112736200A
Self-condensation long-wave mismatch InGaAs battery and preparation method thereof
CN116454146A